Approaches to knowledge-light adaptation in case-based reasoning for radiotherapy treatment planning - Khussainova, Gulmira (2016)
In radiotherapy, ionised radiation beams are used to destroy cancerous cells. A radiotherapy treatment plan needs to be created to deliver a sufficient radiation dose to cancerous cells while sparing nearby organs at risk and healthy tissue. The development of such a treatment plan is a time consuming trial and error process which can take from a few hours up to a few days.